Underjungle : a novel / James Sturz. - Sturz, James (Unnamed Press, 2023)
In Underjungle, an intelligent life form known as the yc exist in the ocean's depths, an apex predator among most fish. Long ago, this species fractured from a single group into seven distinct tribes, each with their own dialect and cultural idiosyncrasies. Now, one tribe, the Gjala, has stumbled across a most intriguing and unusual object: a sunken corpse. As news travels across the ocean, and the other tribes converge to investigate, the consequences and questions raised will reverberate for generations to come.